GAMBARAN KUALITAS TIDUR PADA REMAJA DENGAN KECENDERUNGAN GAME ONLINE - Dessi Purnamasari (Jurnal Nurse, 2021)
Teenagers are considered more often and more prone to online game addiction than adults. As a result, adolescents who are addicted to online games tend to be less interested in other activities and feel restless when they cannot play online games and poor sleep quality and sleep deprivation are common among students. For students who make good use of time between study, play and sleep have a very related relationship. Students who are able to divide their time between studying, playing and socializing, these students can have sufficient quality sleep so that their sleep is of quality, but not all students have coping skills to manage study time and socialize so that sleep time is reduced. In this study it can be concluded that the majority who play online games are 15 years old, as many as 37 (82.2%) respondents, the gender of respondents who play online games is mostly male, as many as 30 people (66.7%), respondents who always play online games as many as 23 people (51.1%), and respondents who have poor quality as many as 33 people (73.3%). Â